The parameters of macrohemodynamics and microcirculation in donors during blood donation - E. M. Lipnitsky; M. R. Gasanov (Сеченовский вестник)
Blood loss 300 ml does not cause significant hemodynamic disorders, however, at the level of the microvasculature, there is an increase in the number of blood cells moving at a slow speed. The most pronounced changes take place when the amount of donated blood is up to 500 ml, revealing a distinct upward trend. The increased linear and volumetric blood flow rate parameters fluctuated with upward trend. Indices of blood flow demonstrated multidirectional dynamics: the ripple index and the index of peripheral resistance showed a downward trend, the index of arterial stenosis showed an upward trend. The values were measured with “Minimax-Doppler-K” device developed and tested in the Institute of Biomedical Problems of the RAS.